Amino-hybridized azole framework-based wide temperature range flame-retardant electrolyte and preparation method thereof
Patent Information
- Application Number
- CN202610935481.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-23
AI Technical Summary
[0009]本发明为解决现有技术中存在的宽温域适应性差、离子导率低和电解质阻燃性能差的问题,提供一种基于氨基杂化氮唑框架的宽温域阻燃电解质及其制备方法
[0028]1)本发明以锂盐和丁二腈分别作为氢键受体与氢键供体所形成的深共晶溶剂具有极低的熔点,在极低温度下仍能保持液态,从而提升了电解质的低温适应性;同时,加入具有阻燃作用的单体DEVP,使电解质在高温环境下不易自燃,显著提高了电池的安全性。
Smart Images

Figure CN122968423A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of crystalline hybrid nitrazole framework and energy storage battery materials, specifically to a wide-temperature-range flame-retardant electrolyte based on an amino-hybrid nitrazole framework and its preparation method. Background Technology
[0002] Electrolytes are a core component of lithium-ion batteries. They not only isolate the positive and negative electrodes and provide an efficient transport channel for lithium ions (Li⁺), thus ensuring the battery's electrochemical performance, but also maintain the battery's internal electrochemical homeostasis, ensuring the stability and continuity of electrode interface reactions. However, the liquid electrolytes commonly used in lithium-ion batteries currently suffer from inherent defects such as volatility, leakage, flammability, and explosiveness. Furthermore, they have a narrow operating temperature range and poor high-temperature stability, easily leading to thermal runaway and other safety hazards, severely hindering the further development of high-performance lithium-ion batteries. Therefore, developing solid-state electrolytes with excellent ion conductivity, high safety, and wide-temperature-range flame-retardant properties is of paramount importance for comprehensively improving the energy density, operational stability, and intrinsic safety of lithium-ion batteries.
[0003] Deep eutectic electrolytes (DEEs) are eutectic systems formed by two or more solid components through hydrogen bonding or coordination, and exist in a liquid or gel state at room temperature. Benefiting from strong intermolecular interactions between components, DEEs possess low glass transition temperatures, wide electrochemical windows, good thermal / chemical stability, low cost, non-toxicity, and high structural flexibility, making them a key strategy for achieving wide-temperature-range battery performance. However, several problems remain due to low ion transport numbers, poor electrode interface compatibility, high bulk viscosity leading to insufficient ionic conductivity, and the susceptibility of some components to side reactions or corrosion during electrochemical cycling.
[0004] The document with publication number "CN120165065A" discloses "A Deep Eutectic Electrolyte and Its Preparation Method, Zinc-ion Battery and Power Device". This method uses zinc salt as a hydrogen bond acceptor and alcohol solvent and water as hydrogen bond donors. Although its preparation method is simple and environmentally friendly, it still has the following shortcomings:
[0005] First, the judgment was based solely on the clarity of the appearance and the battery cycle performance, without testing key parameters such as the ionic conductivity and electrochemical window of the electrolyte.
[0006] Secondly, it only verified the excellent performance of the electrolyte under low temperature conditions, but did not examine its performance under high temperature conditions.
[0007] The document with publication number "CN117013100 A" discloses "A Deep Eutectic Electrolyte and Its Preparation Method, and an Aqueous Zinc-Ion Battery." This method involves mixing a hydrogen bond donor and a hydrogen bond acceptor to obtain a deep eutectic solvent; adding zinc salt, lithium salt, and water to the deep eutectic solvent yields a deep eutectic-based electrolyte. However, it still suffers from poor high-rate performance and requires improvement in long-term cycle stability. This battery operates at low current density (0.2 A g). -1 It exhibits excellent performance under these conditions, with a discharge specific capacity reaching 589 mAhg. -1 However, when the current density increases to 4 A g... -1 At that time, the initial specific capacity decreased to 530 mAh g. -1 This limits its application in scenarios requiring high power output.
[0008] Current research on applying metal-organic framework (MOF) materials to deep eutectic electrolytes (DEEs) mainly focuses on utilizing their intrinsic physical porosity to accommodate liquid components. Due to the limitations of their intrinsic properties and the lack of targeted chemical modification, the interaction between MOF and electrolyte interfaces is weak, and the effect on improving ionic conductivity is not significant. Summary of the Invention
[0009] To address the problems of poor wide-temperature adaptability, low ionic conductivity, and poor flame retardant performance of electrolytes in existing technologies, this invention provides a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrazole framework and its preparation method.
[0010] To achieve the above objectives, the technical solution adopted in this invention is: a method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrazole framework, the method steps of which are as follows:
[0011] Step 1: Dissolve zinc salt, 5-aminotetrazole and carboxylic acid ligand in solvent, stir evenly at room temperature, heat the mixture at high temperature; after slowly cooling to room temperature, filter to obtain powder A;
[0012] Step 2: In an argon-filled glove box, diethyl vinyl phosphate (DEVP) and acrylate monomers are mixed with N,N-methylene acrylamide (MBA) as polymer monomers to obtain solution B;
[0013] Step 3: Add lithium salt and succinate (SN) to solution B, stir vigorously to dissolve them, and obtain a transparent solution C;
[0014] Step 4: Add initiator and powder A to transparent solution C, and continue stirring to obtain polymerizable flame-retardant electrolyte precursor solution D;
[0015] Step 5: Transfer solution D to a small oven and obtain a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrazole framework through in-situ thermal polymerization.
[0016] Furthermore, the zinc salt in step one is zinc acetate, zinc nitrate, or zinc chloride;
[0017] The carboxylic acid ligand is 2-methyl-3H-benzimidazole-5-carboxylic acid, pyromellitic acid, 5-aminoisophthalic acid, or 5-amino-2,4,6-triiodoisophthalic acid;
[0018] The solvent is one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), methanol, or deionized water.
[0019] Furthermore, the molar ratio of zinc salt, 5-aminotetrazole, and carboxylic acid ligand in step one is 1-5:1-5:0.4-2.
[0020] Furthermore, the acrylate monomers in step two are methyl methacrylate (MMA), butyl acrylate (BA), ethyl acrylate (EA), 2-ethylhexyl acrylate (2-EHA), isooctyl acrylate, or lauryl acrylate (LA).
[0021] Furthermore, in step two, the molar ratio of diethyl vinyl phosphate (DEVP), acrylate monomer, and N,N-methylene acrylamide (MBA) is 0.5-1:0.5-1:0.25-1.0.
[0022] Furthermore, in step three, the lithium salt is lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), or lithium hexafluorophosphate (LiPF6).
[0023] Furthermore, in step three, lithium salt is added first, with a mass ratio of lithium salt to solution B of 1:1, and then succinate (SN) is added with a molar ratio of 1:1 to lithium salt.
[0024] Furthermore, in step four, the initiator is azobisisobutyronitrile (AIBN), and the amount added is 1% of the total mass of the polymer monomers; the amount of powder A added is 10% of the total mass of the lithium salt and polymer monomers.
[0025] Furthermore, in step five, the heating temperature is 60-100℃, and the time is 10-24 hours.
[0026] The above preparation method produces a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework.
[0027] Compared with the prior art, the beneficial effects of the present invention are:
[0028] 1) The present invention uses lithium salt and succinate as hydrogen bond acceptors and hydrogen bond donors respectively to form a deep eutectic solvent with an extremely low melting point, which can remain liquid at extremely low temperatures, thereby improving the low-temperature adaptability of the electrolyte; at the same time, the addition of DEVP monomer with flame retardant effect makes the electrolyte less prone to spontaneous combustion in high-temperature environments, which significantly improves the safety of the battery.
[0029] 2) On one hand, the amino-modified hybrid azole framework material synthesized by the solvothermal method possesses an ordered pore structure, which is beneficial for the rapid migration of lithium ions. Simultaneously, the amino groups on the framework can provide additional coordination sites for lithium ions, thereby broadening the ion transport pathway. On the other hand, the amino groups, as strong nucleophiles, can undergo efficient Michael addition reactions with acrylate monomers, chemically linking the hybrid azole framework material to the polymer network. This covalent connection method allows the framework material to be more uniformly dispersed in the polymer matrix, thus more effectively promoting the rapid transport of lithium ions and increasing the transport rate. Experiments have demonstrated a lithium ion transference number of 0.65 and an ionic conductivity of 0.73 mS / cm. -1 .
[0030] 3) This invention employs an in-situ thermally initiated polymerization process, which eliminates the need for high-temperature heating when preparing deep eutectic solvents. The solvents can be obtained at room temperature by stirring, thus avoiding the complex temperature control equipment and long heating steps required by traditional methods. Furthermore, no additional highly reactive initiator is required; polymerization can be completed using only a trace amount of azobisisobutyronitrile (AIBN) in the system. The entire operation is carried out under normal pressure, making it simple, convenient, and easy to operate, facilitating large-scale production and widespread application.
[0031] 4) The method of this invention uses metal-organic framework (MOF) materials. Due to their unique porous structure and the synergistic effect of surface amino groups, they can generate strong chemical bonding with electrolyte components (such as Lewis acid-base interactions). By modifying the functional groups of the metal-organic framework, the ionic conductivity is greatly improved, breaking through the limitations of traditional physical blending.
[0032] 5) This invention is the first to combine a wide temperature range with a flame-retardant electrolyte and modify it with a metal-organic framework (MOF), providing a new preparation method for battery electrolytes. This method can be used in any lithium / sodium / potassium alkaline metal battery, greatly improving the applicability of the material. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the preparation process of the wide-temperature-range flame-retardant electrolyte with an amino-hybridized nitrogen azole framework of the present invention;
[0034] Figure 2 The structure and XRD pattern of the amino-hybrid nitrazole framework crystal material (AHF-2-NH2) synthesized in Example 1 are shown.
[0035] Figure 3 The structure and XRD pattern of the amino-hybridized nitrazole framework crystal material (AHF-5) synthesized in Example 2 are shown.
[0036] Figure 4 The structure and XRD pattern of the amino-hybridized nitrazole framework crystal material (AHF-8) synthesized in Example 3 are shown.
[0037] Figure 5 The structure and XRD pattern of the amino-hybridized nitrazole framework crystal material (AHF-2-NH2-I) synthesized in Example 4 are shown.
[0038] Figure 6 This is a comparison diagram of the states of the amino-hybridized nitrogen azole framework wide-temperature-range flame-retardant electrolyte prepared in this invention before and after polymerization;
[0039] Figure 7 This is a flame retardant performance diagram of the amino-hybrid nitrogen azole framework wide-temperature-range flame retardant electrolyte prepared in this invention;
[0040] Figure 8 This is a graph showing the relationship between time and current when the wide-temperature-range flame-retardant electrolyte prepared in this invention without the addition of an amino-modified hybrid azole framework is applied to a lithium-ion battery.
[0041] Figure 9 This is a graph showing the relationship between time and current when the wide-temperature-range flame-retardant electrolyte with an amino-modified hybrid azole framework prepared in this invention is applied to a lithium-ion battery.
[0042] Figure 10 This is a graph showing the relationship between temperature and ionic conductivity of the wide-temperature-range flame-retardant electrolyte with an amino-hybridized nitrogen azole framework prepared according to the present invention when applied in lithium-ion batteries.
[0043] Figure 11 This is a graph showing the relationship between efficiency and specific capacity of the wide-temperature-range flame-retardant electrolyte with an amino-hybridized nitrogen azole framework prepared in this invention, applied to a lithium-ion battery at a rated capacitance of 0.2 C after 140 cycles. Detailed Implementation
[0044] The present invention provides a method for preparing a wide-temperature-range flame-retardant deep eutectic electrolyte with an amino-hybridized azole framework, comprising the preparation of a metal-organic framework material, the preparation of a polymerizable flame-retardant deep eutectic, and the assembly of the two with a positive electrode and a negative electrode to form a lithium-ion battery.
[0045] This invention successfully prepared a deep eutectic electrolyte with high ionic conductivity and intrinsic flame retardant properties. By incorporating an amino-modified hybrid azole framework material into a polymerizable flame-retardant deep eutectic electrolyte, it effectively replaced the traditional liquid electrolyte, providing a novel approach for designing wide-temperature-range flame-retardant deep eutectic electrolytes based on hybrid azole framework materials.
[0046] The present invention will be further described below with reference to specific embodiments.
[0047] Example 1
[0048] Preparation methods of wide-temperature-range flame-retardant electrolytes based on amino-hybridized nitrazole frameworks, such as... Figure 1 As shown, the steps are as follows:
[0049] Step 1: Dissolve zinc nitrate, 5-methyltetrazole and 5-aminoisophthalic acid in N,N-dimethylformamide (DMF) in a molar ratio of 1:1:1. Stir at room temperature for 30 minutes, then pour the mixture into a 25 mL high-pressure autoclave lined with polytetrafluoroethylene (PTFE). Heat at 120°C for 1 day, then slowly cool the autoclave to room temperature and filter to obtain powder A.
[0050] Step 2: In an argon-filled glove box, diethyl vinyl phosphate (DEVP) and ethyl acrylate (EA) as polymer monomers, along with N,N-methylene acrylamide (MBA), were mixed at a molar ratio of 1:1:0.25 to obtain solution B, with a total mass of 0.481 g.
[0051] Step 3: First, add 0.481 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to solution B, then add succinate (SN) with a molar ratio of 1:1 to lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), stir vigorously to dissolve, and obtain a transparent solution C;
[0052] Step 4: Add 1% by weight of azobisisobutyronitrile (AIBN) and 0.0962g of powder A to the transparent solution C, and continue stirring to obtain polymerizable flame-retardant electrolyte precursor solution D;
[0053] Step 5: Transfer solution D to a 60℃ small oven and heat it in situ for 12 hours to obtain a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrogen azole framework.
[0054] Example 2
[0055] A method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework, comprising the following steps:
[0056] Step 1: Dissolve zinc acetate, 5-aminotetrazole, and pyromellitic acid in deionized water at a molar ratio of 2:2:1. Stir at room temperature for 30 minutes, then pour the mixture into a 25 mL PTFE-lined autoclave and add NaOH. Heat at 170°C for 3 days, then slowly cool the autoclave to room temperature. Filter to obtain powder A.
[0057] Step 2: In an argon-filled glove box, diethyl vinyl phosphate (DEVP) and methyl methacrylate (MMA) as polymer monomers, along with N,N-methylene acrylamide (MBA), were mixed at a molar ratio of 1:1:0.5 to obtain solution B, with a total mass of 0.542 g.
[0058] Step 3: First, add 0.542g of lithium hexafluorophosphate (LiPF6) to solution B, then add succinate (SN) with a molar ratio of 1:1 to lithium hexafluorophosphate (LiPF6), stir vigorously to dissolve it, and obtain a transparent solution C;
[0059] Step 4: Add 1% by weight of azobisisobutyronitrile (AIBN) and 0.1084g of powder A to the transparent solution C, and continue stirring to obtain polymerizable flame-retardant electrolyte precursor solution D;
[0060] Step 5: Transfer solution D to a 60℃ small oven and heat it in situ for 12 hours to obtain a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrogen azole framework.
[0061] Example 3
[0062] A method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework, comprising the following steps:
[0063] Step 1: Dissolve zinc chloride, 5-aminotetrazole, and 2-methyl-3H-benzimidazole-5-carboxylic acid in N,N-dimethylacetamide (DMA) in a molar ratio of 2:2:1. Then add pyrazine and 1 drop of tetramethylammonium hydroxide. Stir well at room temperature, and then heat the mixture in a 25 mL PTFE-lined autoclave at 120°C for 36 h. After slowly cooling to room temperature, filter to obtain powder A.
[0064] Step 2: In an argon-filled glove box, diethyl vinyl phosphate (DEVP) and butyl acrylate (BA) as polymer monomers were mixed with N,N-methylene acrylamide (MBA) at a molar ratio of 1:1:1 to obtain solution B with a total mass of 0.707 g;
[0065] Step 3: First, add 0.707g of lithium perchlorate (LiClO4) to solution B, then add succinate (SN) with a molar ratio of 1:1 to lithium perchlorate (LiClO4), stir vigorously to dissolve it, and obtain a transparent solution C;
[0066] Step 4: Add 1% by weight of azobisisobutyronitrile (AIBN) and 0.1414g of powder A to the transparent solution C, and continue stirring to obtain polymerizable flame-retardant electrolyte precursor solution D;
[0067] Step 5: Transfer solution D to a small oven at 100℃ and heat it in situ for 24 hours to obtain a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrogen azole framework.
[0068] Example 4
[0069] A method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework, comprising the following steps:
[0070] Step 1: Dissolve zinc acetate, 5-methyltetrazole and 5-amino-2,4,6-triiodophthalic acid in N,N-dimethylformamide (DMF) in a molar ratio of 5:5:2. After stirring evenly at room temperature, pour the mixture into a 25 mL high-pressure autoclave lined with polytetrafluoroethylene (PTFE). Heat at 120°C for 3 days. Then, slowly cool the autoclave to room temperature and filter to obtain powder A.
[0071] Step 2: In an argon-filled glove box, diethyl vinyl phosphate (DEVP) and 2-ethylhexyl acrylate (2-EHA) as polymer monomers were mixed with N,N-methylene acrylamide (MBA) at a molar ratio of 1:1:0.25 to obtain solution B, with a total mass of 0.613 g;
[0072] Step 3: First, add 0.613 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to solution B, then add succinate (SN) with a molar ratio of 1:1 to lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), stir vigorously to dissolve, and obtain a transparent solution C;
[0073] Step 4: Add 1% by weight of azobisisobutyronitrile (AIBN) and 0.1226g of powder A to the transparent solution C, and continue stirring to obtain polymerizable flame-retardant electrolyte precursor solution D;
[0074] Step 5: Transfer solution D to a small oven at 100℃ and heat it in situ for 24 hours to obtain a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrogen azole framework.
[0075] Example 5
[0076] A method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework, comprising the following steps:
[0077] Step 1: Dissolve zinc nitrate, 5-methyltetrazole and 5-aminoisophthalic acid in N,N-dimethylformamide (DMF) in a molar ratio of 1:1:1. Stir at room temperature for 30 minutes. Pour the mixture into a 25 mL autoclave lined with polytetrafluoroethylene (PTFE). Heat at 120 °C for 1 day. Slowly cool the autoclave to room temperature and filter to obtain powder A.
[0078] Step 2: In an argon-filled glove box, diethyl vinyl phosphate (DEVP) and isooctyl acrylate as polymer monomers were mixed with N,N-methylene acrylamide (MBA) at a molar ratio of 1:1:0.5 to obtain solution B, with a total mass of 0.674 g;
[0079] Step 3: First, add 0.674 g of lithium tetrafluoroborate (LiBF4) to solution B, then add succinate (SN) with a molar ratio of 1:1 to lithium tetrafluoroborate (LiBF4), stir vigorously to dissolve it, and obtain a transparent solution C;
[0080] Step 4: Add 1% by mass of azobisisobutyronitrile (AIBN) and 0.1348g of powder A to the transparent solution C, and continue stirring to obtain polymerizable flame-retardant deep eutectic electrolyte precursor solution D;
[0081] Step 5: Transfer solution D to an 80℃ small oven and heat it in situ for 18 hours to obtain a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrogen azole framework.
[0082] Of the above embodiments, Embodiment 1 is the preferred embodiment. Referring to the accompanying drawings, it can be seen that:
[0083] like Figure 2 As shown in Figures (a) and (b), the structure of the amino-hybridized nitrazole framework material (AHF-2-NH2) synthesized according to Example 1 is displayed, showing that the material has abundant pore structure and a regular and ordered pore arrangement. Figure (c) is an X-ray diffraction (XRD) pattern, showing sharp and well-matched characteristic diffraction peaks, which are in high agreement with the simulated crystal structure, verifying the successful synthesis of the target product. This high porosity and ordered pore structure provides a structural basis for the rapid transport of ions in the subsequent electrolyte.
[0084] Figure 3 (b) shows the structure of the amino-hybridized azole framework material (AHF-5) synthesized according to Example 2, which uses pyromellitic acid and 5-aminotetrazole as ligands. Figure (a) shows its rich pore structure and orderly pore arrangement synthesized by hydrothermal method. Figure (c) is the XRD pattern, which verifies the successful synthesis of the target product.
[0085] Figure 4 Figure (b) shows the structure of the amino-hybridized azole framework material (AHF-8) synthesized according to Example 3. Figure (b) shows the structure synthesized by a solvothermal method using 2-methyl-3H-benzimidazole-5-carboxylic acid and 5-aminotetrazole as ligands. Figure (a) shows that the structure has abundant pores and regular channels. Figure (c) shows the XRD pattern verifying the successful synthesis of the target product.
[0086] Figure 5The structure of the amino-hybridized nitrazole framework material (AHF-2-NH2-I) synthesized according to Example 4 is shown in Figure (b). Figure (b) shows that this structure, using 5-amino-2,4,6-triiodophthalic acid and 5-methyltetrazole as ligands, exhibits a rich porous structure after solvothermal synthesis. Figure (a) shows its orderly pore arrangement. The XRD pattern in Figure (c) verifies the successful synthesis of the target product. The presence of this structure facilitates rapid ion transport in the electrolyte.
[0087] like Figure 6 As shown in the photographs comparing the states of the electrolyte before and after polymerization, the system was a homogeneous liquid before polymerization; however, after polymerization, it transformed into a self-supporting gel electrolyte membrane with no obvious phase separation. This indicates that the amino-hybridized azole framework has been uniformly and stably integrated into the electrolyte matrix, forming a dense composite electrolyte system with good interfacial compatibility. The introduction of MOF particles not only enhances the mechanical strength of the electrolyte but also prevents the precipitation or aggregation of small molecule flame retardants, ensuring the long-term stability of the system.
[0088] like Figure 7 As shown, both the electrolyte membranes without MOF and those with MOF achieved self-extinguishing within 0.2 s after ignition. This phenomenon is attributed to the formation of a phosphorus-containing cross-linked network during the DEVP polymerization process, which releases phosphorus-containing free radicals upon heating. These free radicals capture H· and OH· radicals in the combustion chain reaction, thereby achieving an intrinsic flame-retardant effect. This mechanism endows the electrolyte with the ability to rapidly self-extinguish under high temperatures or external flame contact, significantly improving the safety of lithium-ion batteries.
[0089] like Figure 8 As shown in the inset, the AC impedance spectra of the same battery before and after polarization are displayed. The calculated lithium-ion transference number is 0.32. This is because the wide-temperature-range flame-retardant electrolyte without the addition of an amino-modified hybrid azole framework lacks obvious anchoring sites for lithium ions and also lacks effective fixation of anions. Therefore, its ability to promote lithium-ion transport is limited, resulting in a low ion transference number.
[0090] Figure 9 The figure shows the time-current relationship of a wide-temperature-range flame-retardant electrolyte with an amino-modified hybrid azole framework. The inset shows the AC impedance spectra of the same battery before and after polarization. The calculated lithium-ion transference number is 0.65, which is mainly attributed to the excellent specific surface area and continuous pore structure of the amino-hybrid azole framework modified electrolyte. The high specific surface area is conducive to the formation of a high concentration of lithium-ion coordination sites, while the regular pores provide directional migration paths, thereby effectively suppressing anion diffusion and promoting selective lithium-ion transport.
[0091] like Figure 10The figure shows the relationship between temperature and ionic conductivity of the amino-hybridized nitrile framework wide-temperature-range flame-retardant electrolyte prepared in Example 1 of this invention when applied to lithium-ion batteries. As the test temperature increases from room temperature to 80 °C, the corresponding ionic conductivity increases with temperature, consistent with Arrhenius behavior. This result indicates that the electrolyte maintains good ionic conductivity over a wide temperature range, demonstrating its excellent wide-temperature-range adaptability, and is particularly suitable for lithium metal battery operating environments under extreme climatic conditions.
[0092] like Figure 11 The figure shows the relationship between efficiency and specific capacity of the lithium-ion battery after 140 cycles at a rated capacitance of 0.2 C, with filter paper cut into 19mm discs for assembly. During assembly, the polymerizable flame-retardant electrolyte precursor solution D obtained in step 4 is dropped onto the separator. After 140 cycles, the battery's discharge specific capacity is 128 mAh / g, and its coulombic efficiency remains around 99%. This excellent performance is attributed to the amino-hybridized nitrile framework modified electrolyte, which possesses both high specific surface area and abundant pore structure. This not only provides a rapid diffusion channel for lithium ions but also suppresses lithium dendrite growth by homogenizing the interfacial lithium ion flow. Therefore, this electrolyte can effectively mitigate the volume change and side reactions of the lithium metal anode during cycling, significantly improving the long-cycle stability and safety of lithium metal batteries.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework, characterized in that: The steps are as follows: Step 1: Dissolve zinc salt, 5-aminotetrazole and carboxylic acid ligand in solvent, stir evenly at room temperature, heat the mixture at high temperature; after slowly cooling to room temperature, filter to obtain powder A; Step 2: In an argon-filled glove box, diethyl vinyl phosphate (DEVP) and acrylate monomers are mixed with N,N-methylene acrylamide (MBA) as polymer monomers to obtain solution B; Step 3: Add lithium salt and succinate (SN) to solution B, stir vigorously to dissolve them, and obtain a transparent solution C; Step 4: Add initiator and powder A to transparent solution C, and continue stirring to obtain polymerizable flame-retardant electrolyte precursor solution D; Step 5: Transfer solution D to a small oven and obtain a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized nitrazole framework through in-situ thermal polymerization.
2. The method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework according to claim 1, characterized in that: In step one: The zinc salts are zinc acetate, zinc nitrate, or zinc chloride; The carboxylic acid ligand is 2-methyl-3H-benzimidazole-5-carboxylic acid, pyromellitic acid, 5-aminoisophthalic acid, or 5-amino-2,4,6-triiodoisophthalic acid; The solvent is one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), methanol, or deionized water.
3. The method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework according to claim 1 or 2, characterized in that: The molar ratio of zinc salt, 5-aminotetrazole and carboxylic acid ligand in step one is 1-5:1-5:0.4-2.
4. The method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework according to claim 3, characterized in that: The acrylate monomers in step two are methyl methacrylate (MMA), butyl acrylate (BA), ethyl acrylate (EA), 2-ethylhexyl acrylate (2-EHA), isooctyl acrylate, or lauryl acrylate (LA).
5. The method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework according to claim 4, characterized in that: In step two, the molar ratio of diethyl vinyl phosphate (DEVP), acrylate monomer, and N,N-methylene acrylamide (MBA) is 0.5-1:0.5-1:0.25-1.
0.
6. The method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework according to claim 5, characterized in that: In step three, the lithium salt is lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), or lithium hexafluorophosphate (LiPF6).
7. The method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework according to claim 6, characterized in that: In step three, lithium salt is added first, with a mass ratio of lithium salt to solution B of 1:1, and then succinate (SN) is added with a molar ratio of 1:1 to lithium salt.
8. The method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework according to claim 7, characterized in that: In step four, the initiator is azobisisobutyronitrile (AIBN), and the amount added is 1% of the total mass of the polymer monomers; the amount of powder A added is 10% of the total mass of the lithium salt and polymer monomers.
9. The method for preparing a wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework according to claim 8, characterized in that: In step five, the heating temperature is 60-100℃ and the time is 10-24h.
10. A wide-temperature-range flame-retardant electrolyte based on an amino-hybridized azole framework prepared by the method described in claim 1.
Citation Information
Patent Citations
Deep eutectic-based electrolyte, preparation method thereof and aqueous zinc ion battery
CN117013100A
Deep eutectic electrolyte, preparation method thereof, zinc ion battery and electric device
CN120165065A